Applied pharmacokinetics & pharmacodynamics : principles of therapeutic drug monitoring - Burton, Michael E.; Shaw, Leslie M.;Schentag, Jerome J.;Evans, William E. (Philadelphia, Pennsylvania : Lippincott Williams & Wilkins, 2006)
The Third Edition of Applied Pharmacokinetics remains the gold standard by which all other clinical pharmacokinetics texts are measured. Written by leading pharmacokinetics researchers and practitioners, this book is the most advanced kinetics reference available. All chapters have been extensively updated or completely rewritten for this edition, and six new chapters have been added on pharmacodynamics, pharmacogenetics, pharmacokinetic considerations in the obese, dietary influences on drug disposition, zidovudine, and corticosteroids. Each chapter is tightly focused on the most important concepts and issues. Chapters on specific drugs are organized in a consistent format for quick, easy information retrieval. Major subheadings include Clinical Pharmacokinetics, Pharmacodynamics, Clinical Application of Pharmacokinetic Data, Analytical Methods, and Prospectus
Part I. Basic Concepts and Principles 1 -- Part II. Monitored Drugs -- Appendix -- Index.
Includes bibliographical references and index.
Keywords: PHARMACOKINETICS